Beyond the circular economy theory: Implementation methodology for industrial SMEs - Vanessa Prieto-Sandoval; Luz Elba Torres-Guevara; Marta Ormazabal; Carmen Jaca (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: The circular economy has multiple benefits and opportunities to achieve sustainability and a better future for the next generations. The purpose of this paper is to propose a methodology that guides step-by-step any industrial SMEs in the transition from the linear to a circular model. Small and medium enterprises (SMEs) have a crucial role in the sustainable development transition, considering that they represent most of the world's companies. Design/methodology/approach: To develop this methodology, two research techniques were used: a focus group and storyboarding. Findings: The resulting methodology, called Ecopyme, comprises five steps: 1) Firm identity, 2) Diagnosis, 3) Planning, 4) Get the ball rolling, and 5) Assessment and feedback. In addition, two key criteria that must be included in the whole process were identified: value creation in the firm through a circular economy and organization commitment from the top management to the staff. Research limitations/implications: The Ecopyme methodology has two limitations: It does not propose either implementation tools or involve consumers and actors at the meso (e.g., Eco-industrial parks) and macro (e.g., cities, provinces, countries) levels. Practical implications: This study will help policymakers understand the SMEs' perspective and remove barriers that may hinder the paradigm shift. The methodology is also a useful tool for consultants and entrepreneurs to incorporate the circular economy (CE) principles into their business. Originality/value: In the CE literature, little attention has been paid to proposing a structured methodology to implement CE in SMEs. Thus, the study provides a step-by-step methodology that guides any industrial SMEs to transition from linear to circular. Also, it provides additional evidence concerning the importance of human commitment in changing firms' paradigm because people can encourage the adoption of responsible production practices if firms commit CEOs, sustainability managers, and staff.
Keywords: 650; Circular economy implementation; strategic management; sustainable improvement; SMEs; storyboarding